Skeleton - Parker, Steve (London Dorling Kindersley Limited, 1990)
This reference book gives detailed information on the skeleton. It has been structured so that the individual themes of each spread make up a complete visual story and a self-contained module of information. It is part of the "Eyewitness Guides" series.
Keywords: Anatomy